2013
DOI: 10.1002/jhbp.19
|View full text |Cite
|
Sign up to set email alerts
|

Non‐operative management of blunt liver injury: a new protocol for selected hemodynamically unstable patients under hypotensive resuscitation

Abstract: All the selected unstable patients were successfully managed non-operatively after the protocol revision. The decrease in laparotomy rates and transfusion requirements confirmed the feasibility of our new protocol for these selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Recent studies have indicated that the selective nonoperative management of blunt hepatic and splenic injuries is a feasible strategy, even for hemodynamically unstable patients or those with a high grade of injuries. [ 19 , 20 ] Our present findings are consistent with these previous results, which implies that selectively performing CT scans would help physicians reduce unnecessary laparotomy in hemodynamically unstable patients.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have indicated that the selective nonoperative management of blunt hepatic and splenic injuries is a feasible strategy, even for hemodynamically unstable patients or those with a high grade of injuries. [ 19 , 20 ] Our present findings are consistent with these previous results, which implies that selectively performing CT scans would help physicians reduce unnecessary laparotomy in hemodynamically unstable patients.…”
Section: Discussionsupporting
confidence: 92%
“…Most prior studies concluded that the main reason for the failure of NOM is the hemodynamic instability, whereas this observation was contradicted by Mitsusada et al [ 23 ]. Various predictors of NOM failure have been documented in the literatures [ 2 , 9 , 13 , 24 26 ].…”
Section: Discussionmentioning
confidence: 97%
“…According to the study of Miller et al [ 14 ], the failure rate of NOM attempted for high-grade BSI improved from 15% to 5% with the incorporation of a protocol. Mitsusada et al [ 23 ] reported that NOM of BHI applied for selected hemodynamically unstable patients (target SBP of 80 mmHg) under a revision protocol can decrease the overall laparotomy rates and transfusion requirements. Accordingly, a protocol based algorithm for the management of BHSI is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 of them were excluded because they did not focus on the primary subject, 5 of them were excluded because they were case reports and 2 of them were excluded because they were not written in the English language. Finally, a total of 10 studies were included in the review [9][10][11][12][13][14][15][16][17][18]. Almost all of them were retrospective studies and only one was an observational study.…”
Section: Resultsmentioning
confidence: 99%